1963
DOI: 10.4049/jimmunol.91.6.757
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antibodies against Aeromonas Salmonicida in Trout

Abstract: Summary The development of agglutinating antibody to Aeronomas salmonicida in brook and brown trout was demonstrated by a tube agglutination and a rapid slide agglutination test. Comparison of agglutinin titer development in rabbits and trout demonstrated that trout have a slow antibody response reaching maximum titer about 3 months after injection. Rabbits developed peak titers within a month after receiving the same dose of antigen. Trout immunized with a single injection of formalin-killed ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…They are, however, still elevated compared to the non-vaccinated controls. Krantz et al showed elevated antibody levels in brown trout after an oil adjuvanted vaccination, sustaining the increased levels for at least 24 months [8]. Bricknell et al showed elevated antibody levels after un-adjuvanted vaccination of salmon, lasting at least 9 months [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They are, however, still elevated compared to the non-vaccinated controls. Krantz et al showed elevated antibody levels in brown trout after an oil adjuvanted vaccination, sustaining the increased levels for at least 24 months [8]. Bricknell et al showed elevated antibody levels after un-adjuvanted vaccination of salmon, lasting at least 9 months [11].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the effects of vaccination have been performed on salmon, possibly due to their economic role in modern aquaculture. However, some works have focused on rainbow trout, from the initial attempts on vaccination made by Duff in the 1940's [3], over later immunization studies by Krantz et al [8], and on to the work of Hastings, Stapleton and Ellis on the antibody responses towards extracellular products of A. salmonicida [12,13]. This study was initiated to provide a collected view of the role of antibodies in the induction of protection induced by the dominant oil adjuvanted i.p.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations